Exploitation of Host Cell Biology and Evasion of Immunity by Francisella Tularensis - Abu Kwaik, Yousef; Asare, Rexford (Frontiers in Microbiology, 2011)
Francisella tularensis is an intracellular bacterium that infects humans and many small mammals. During infection, F. tularensis replicates predominantly in macrophages but also proliferate in other cell types. Entry into host cells is mediate by various receptors. Complement-opsonized F. tularensis enters into macrophages by looping phagoscytosis. Uptake is mediated in part by Syk, which may activate actin rearrangement in the phagocytic cup resulting in the engulfment of F. tularensis in a lipid raft rich phagosome. Inside the host cells, F. tularensis resides transiently in an acidified late endosome-like compartment before disruption of the phagosomal membrane and escape into the cytosol, where bacterial proliferation occurs. Modulation of phagosome biogenesis and escape into the cytosol is mediated by the Francisella pathogenicity island-encoded type VI-like secretion system. Whilst inside the phagosome, F. tularensis inhibits NADPH oxidase activity but temporarily inducing pro-inflammatory cytokines in PI3K/Akt-dependent manner, which is counteracted by the induction of SHIP that negatively regulates PI3K/Akt activation and promotes bacterial escape into the cytosol. Interestingly, F. tularensis subverts CD4 T cells-mediated killing by inhibiting antigen presentation by activated macrophages through ubiquitin dependent degradation of MHC II molecules on activated macrophages. In the cytosol, F. tularensis is recognized by the host cell AIM2-dependent inflammasome, which is down-regulated by F. tularensis that also inhibits Caspase-1 and ASC activity. During late stages of intracellular proliferation, caspase-3 is activated but apoptosis is delayed through activation of NF-kB and Ras, which ensures cell viability.